Search patterns - Morville, Peter (O'Reilly Media, 2010)
This provocative and inspiring book explores design patterns that apply across the categories of web, ecommerce, enterprise, desktop, mobile, social, and realtime search and discovery. Using colorful illustrations and examples, the authors bring modern information retrieval to life, covering such diverse topics as relevance ranking, faceted navigation, multi-touch, and augmented reality together with a practical guide to help us make search better today.